Performance, Lipid, and Omega Fatty Acids Composition of Village Chickens Fed Diet Supplemented with Flaxseed Oil - Farahiyah, I. J.; Lokman Hakim, I.; Mardhati, M.; Nurulhayati, A. B.; Hafandi, A.; Noraini, S. (Tropical Animal Science Journal, 2025)
Flaxseed oil is a rich source of omega fatty acids and has gained attention as a functional feed additive in the poultry industry. While the use of flaxseed oil in poultry has been widely reported, its application in village chickens remains limited, particularly regarding its physiological and metabolic effects. Thus, this study aimed to determine the effect of flaxseed oil (FO) supplementation on growth performance, carcass yields, and omega fatty acid levels in village chickens. A total of 120 village chickens (with average body weight 606.80 g) were randomly divided into four treatment groups with five replicates. Three levels of FO inclusion were experimented to replace palm oil used in the control treatment, where T0-basal diet with no FO, T1-2.5% FO inclusion, T2-3.0% FO inclusion, and T3-4.0% FO inclusion. Chickens were fed these experimental diets for five weeks, after which they were slaughtered. Breast and thigh muscles were collected for lipid and fatty acid analysis. Weight gain was slightly compromised as higher incorporation of FO was added to the diet of this village chicken (p<0.05). No significant differences were observed in carcass yield (p>0.05) between the treatments. Lipid composition in breast muscle increased with increasing addition of FO (p>0.05), but all FO treatments were found to be lower than control (p<0.05). However, in the thigh muscle, chickens in treatment T2 (3.0% FO inclusion) had the highest composition among FO diets but much lower compared to the control (p<0.05). Alpha-linolenic acids (ALA) in both breast and thigh muscles showed an increasing trend as a higher inclusion of FO was added (p<0.05) compared to the control and slightly reduced at 4.0% inclusion. In conclusion, the supplementation of flaxseed oil had no negative impact on the growth performance and carcass yields of village chickens while significantly enhancing the omega-3 fatty acid content in both breast and thigh muscles.